The Urgency of Fiqh Muamalat Education in Community Life: A Review of Islamic Education in the Digital Era - Irfan Nufa Sagita; Moh. Danil Handika; Rika Awania; Atiya Arifiyanah (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
The low level of fiqh muamalat literacy amidst widespread economic digitalization has contributed to serious socio-economic problems threatening the welfare of Muslim communities. Data from the Financial Services Authority (OJK) and Statistics Indonesia (BPS) in 2024 recorded an Islamic financial literacy index of only 39.11%, far behind the 65.43% conventional financial literacy rate. This paradox is evident: Islamic financial inclusion continues to grow, yet public understanding of the underlying contracts remains alarmingly low. This gap is reflected in the proliferation of 2,481 illegal online lending platforms blocked between January 2023 and February 2024 (OJK, 2024), usurious paylater schemes, gharar-laden e-commerce transactions, and online gambling generating IDR 327 trillion in fund flows throughout 2023 (PPATK, 2024). This study employed a library research method with a pedagogical-sociological approach grounded in Vygotsky's social constructivism theory. The study argues that the root cause of all these problems lies in the failure of the doctrinal-textual curriculum approach to fiqh muamalat, not in individual moral failure. Three key findings emerged: first, the fiqh muamalat literacy crisis is structural in nature and poses a real threat to the socio-economic resilience of the Muslim community; second, the fiqh muamalat curriculum must shift from legal doctrine toward the internalization of seven character values; third, ten contextual learning strategies grounded in social constructivism represent the most relevant and effective approach. Revitalizing fiqh muamalat education through the Three Educational Centers synergy is key to producing a generation of Muslims who are Islamically economically literate and financially empowered.